I shake hands before I penetrate: Scientific essay - Uri, Helene (Nordic Journal of Art & Research, 2020)
In this essay, I explore what artistic research implies for me as a novelist and as an artistic researcher. The point of departure is the young adult novel Stillheten etterpå (2019), and the primary goal is to find out more about how characters in fiction are created. I use examples from a wide range of my novels, but the focus is on the process of writing Stillheten etterpå. I confess my hesitation towards reasoning about my own (fictional) writing. However, by working with this essay I have learnt more about my creative process. I discuss for instance how a change in point of view is a method I find useful. But several aspects of the creative process remain inexplicable, and I conclude that this is how it should be.